Requirements for the Development of Educational Activities in Primary School, Pedagogical Conditions and Principles of Activities to Improve the Interests of Readers - Abdukhamidova, B.A.; Aidarova , c.p.s. M. D.; Aktilek, c.p.s. Ergeshalikyzy; Aimankul, Aldash; Assel , Seidamat (Journal of Ecohumanism, 2025)
The article discusses the requirements and pedagogical conditions for the formation of reading competence, motivation for the art of the work, awakening, development of reading interest of primary school students. In particular, it takes into account the fact that children will have different interests, different requirements; motivate children's interest in reading; help a child read books as a reader; distribute books among young readers; take into account the criteria and principles for selecting texts for reading; take into account the text, type of work and genre diversity; diversity of speech in texts for to use the ability to illustrate with the correct understanding of the text; the graphic and artistic quality of the recommended book for reading; the correspondence of the plot and compositional construction of the work to the age and perception of the child; adaptation of texts presented in the textbook to students of this class; the text notes that such requirements as compliance with the norm of word ratio should be taken into account. Guided by general didactic principles, it was noted that along with them there are a number of principles that should be taken into account in the activities of preparing and motivating the reader to read in the lessons of literary reading and highlighted the main points. In addition, it should be noted that there are principles of focusing attention when performing written works based on the work read, parallel reproduction of the work read with the mental activity of students with a special emphasis on the educational value of the work presented for reading. Each principle is illustrated by some examples that help the teacher's activities, regulates his activities in the field of educating the reader.